THE INCIDENCE OF SYSTEMIC DISEASES IN DENTAL PRACTICE AND THE READINESS OF DENTISTS IN THEIR MANAGEMENT - Tichvy Tammama; Saskia Lenggogeni Nasroen; Raeny Mutiara Dewi (Fakultas Kedokteran Gigi Unjani, 2023)
Systemic disease is a medical condition that can affect dental care and cause complications during and after dental treatment, so it needs special attention and treatment by dentists. Systemic diseases consist of heart disorders and hypertension, diabetes, blood disorders, and others. The purpose of this study is to determine the readiness of dentists to treat patients with systemic diseases. The study was conducted by distributing questionnaires in an electronic form to dentists in West Bandung Regency (KBB) and its surroundings in the form of experience in finding patients with systemic diseases in practice and readiness in their management. Questionnaires were obtained from 83 dentists, with the results describing that 98.8% of dentists had treated patients with systemic diseases. Systemic diseases that were often found in practice are hypertension (96.2%), then diabetes (89.2%), heart disorders (65.1%), asthma (47%), allergies (45.8%), stroke (37.3%), blood disorders (27.7%), kidney disorders (25.3%), thyroid disorders (24.1%), liver disorders (14.5%), and others (2.4%). The results show that dentists in the KBB area were well-prepared to treat patients with systemic diseases. Dental and oral care in patients with systemic diseases were found in daily practice. Based on the research results, most dentists have encountered patients with systemic diseases and are ready to treat patients with controlled systemic diseases. However, when the systemic disease conditions are not governed, the dentist chooses to consult the patient with a general practitioner or internal medicine specialist first. Most dentists in the West Bandung Regency and its surroundings have found patients with systemic diseases who were well-prepared for their management plans at their practice sites. DOI : 10.54052/jhds.v2n3.p489-500